2018
DOI: 10.15376/biores.13.1.2035-2048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrophobic Modification on Mechanical Properties of Chinese Fir Wood

Abstract: The water repellency, elastic modulus, and hardness of hydrophobictreated and untreated wood cell walls were investigated. Chinese fir (CF; Cunninghamia lanceolata (Lamb.) Hook) wood was modified using polydimethylsiloxane (PDMS) and dimethyldichlorosilane (DMDCS) dissolved in n-hexane at 2%, 5%, and 8% (w/w) for 5 min, 30 min, and 2 h, respectively. A hydrophobic property was observed in the modified wood. The water contact angle value of the untreated wood surface was 85°, but after treatment this value incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Compared with Curve A for the raw material, in Curve B, the peak intensities at 1100 cm −1 and 3000–3700 cm −1 decrease, indicating the dehydration of EHL. Therefore, a comparison of Curves A and B shows that dehydration and aromatization occurred during the HTC of EHL, and many oxygen-containing functional groups such as C=O and C-O were present on the surface of the synthesized CSs 37 , 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with Curve A for the raw material, in Curve B, the peak intensities at 1100 cm −1 and 3000–3700 cm −1 decrease, indicating the dehydration of EHL. Therefore, a comparison of Curves A and B shows that dehydration and aromatization occurred during the HTC of EHL, and many oxygen-containing functional groups such as C=O and C-O were present on the surface of the synthesized CSs 37 , 38 .…”
Section: Resultsmentioning
confidence: 99%
“…The microstructure and surface morphology of the samples were examined via field emission scanning electron microscopy (FE-SEM) (S4800, HITACHI, Tokyo, Japan). The samples were attached to an aluminum specimen mount with conductive carbon tape (Yang et al 2018a) and sputter coated with gold under vacuum at 20 mA for 20 min. The samples were observed and imaged at an accelerating voltage of 5 kV.…”
Section: Micromorphological Featuresmentioning
confidence: 99%
“…To explore the relationship between wood properties and chemical compositions, there has been a wealth of research conducted on removing the chemical components from wood cell walls through a chemical method. Moreover, the chemical composition of wood is found to have a significant influence on the mechanical properties [ 1 , 2 , 3 ]. It is also found that a decline in hemicellulose affects the integrity of the cell wall polymers and decreases the strength against mechanical loads.…”
Section: Introductionmentioning
confidence: 99%